2011
DOI: 10.1109/tap.2010.2096191
|View full text |Cite
|
Sign up to set email alerts
|

Compact Coplanar Waveguide (CPW)-Fed Zeroth-Order Resonant Antennas With Extended Bandwidth and High Efficiency on Vialess Single Layer

Abstract: ease of fabrication and good performance the proposed ZOR may find applications in wireless communication systems. IEEE Trans Microwave Theory Tech 61 (2013) 9. D.K. Upadhyay, S. Pal, An improved zeroth order resonator using left handed metamaterial, J Microwaves Optoelectron Electromag Appl 12 (2013), 131-140. 10. M.A. Abdalla and Z. Hu, Design and analysis of tunable left handed zeroth-order resonator on ferrite substrate, IEEE Trans Magn 44 (2008), 3095-3098. 11. C. Caloz and T. Itoh, Electromagnetic Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
126
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 21 publications
1
126
0
Order By: Relevance
“…5(b). It can be observed that all the vectored electric field lines throughout the patch are perpendicular and in the same phase, hence ZOR [31]. Additionally Fig.…”
Section: Proof Of Metamaterialsmentioning
confidence: 84%
“…5(b). It can be observed that all the vectored electric field lines throughout the patch are perpendicular and in the same phase, hence ZOR [31]. Additionally Fig.…”
Section: Proof Of Metamaterialsmentioning
confidence: 84%
“…The CRLH-TL can also be used to design dual-band/multi-band antennas [13], circularly polarized antennas [18], and reconfigurable antennas [19], using their different resonant modes. Recently, the concept of CRLH TL has been introduced for coplanar waveguides (CPW) [20][21][22], and substrate integrated waveguides (SIW) [23,24], which results in features like wide bandwidth and high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a great effort on miniaturized [16][17][18], multi-band [19][20][21] or leaky-wave [22][23][24] antennas based on the concept of metamaterials. Nevertheless, from the authors' point of view, the multi-band and/or multifunction antennas based on combination of the metamaterials and monopole antenna have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%